2011
DOI: 10.1002/app.34298
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated weathering of pectin/poly(vinyl alcohol) blends studied by spectroscopic methods

Abstract: The blends of pectin (PEC) and poly(vinyl alcohol) (PVA) at different components ratios were prepared by mixing in water. Thin polymeric films of PEC/ PVA blends and pure polymers were obtained by casting method. All samples were then artificially aged using Suntest apparatus (Atlas) up to 780 h. The changes in chemical structure during sample ageing have been monitored by infrared and ultraviolet-visible absorption spectroscopies. The first stage of weathering (up to $ 300 h) was very slow and alteration of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 43 publications
4
26
0
Order By: Relevance
“…The deviations of log η a decrease with the increase of the temperature and with the increase of shear rate. Such behaviour suggests that PEC with PVA is poor or immiscible, which was also suggested in the previous works concerning these blends [11,12]. in the experiment carried out up and down [9].…”
Section: Flow Propertiessupporting
confidence: 55%
See 3 more Smart Citations
“…The deviations of log η a decrease with the increase of the temperature and with the increase of shear rate. Such behaviour suggests that PEC with PVA is poor or immiscible, which was also suggested in the previous works concerning these blends [11,12]. in the experiment carried out up and down [9].…”
Section: Flow Propertiessupporting
confidence: 55%
“…The amount of methyl esterified groups in pectin, equal to 27.8%, was estimated by FTIR spectroscopy [12] as the ratio of integral intensity of band attributed to methyl esterified carboxylic groups (A 1739 ) and the sum of areas of ester and carboxyl bands (A1739+A1612).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that ageing causes an increase in the transparency and converts these blends to small fragments after 30 days. The accelerated weathering of the pectin/PVA blend was studied by exposing the samples for 780 h [18] . Changes in the hydroxyl and carbonyl peaks of the blends in the Fourier transfer infrared spectroscopy (FTIR) spectra indicate the photo-oxidation of the polymer chains.…”
Section: Introductionmentioning
confidence: 99%